A van der Waals CaCl semiconducting electrene and ferromagnetic half-metallicity induced by superhalogen decoration. (August 2022) - Chen, Ying; Wang, Guangzhao; Yuan, Hongkuan; Chen, Hong
Abstract: Electrides, with excess electrons confined in interstitial spaces, are promising for the use in catalysis, electron emitters, superconductors, and spintronics. However, they tend to lack chemical stability and magnetism, which limits their practical applications. In this work, using the first-principles calculations, we report a scarce layered semiconducting electride CaCl with P 3 ̅ m 1 symmetry. The exfoliated CaCl monolayer from the bulk retains the semiconducting electride with extremely low exfoliation energy (0.17 J/m 2 ), high in-plane stiffness (24.35 N/m), high electron mobility (597 cm 2 V −1 s −1 ), and low work function (3.67 eV). Such a CaCl electrene is confirmed to be thermodynamically stable by negative formation enthalpy, no imaginary frequency of phonon dispersion, ab initio molecular dynamics simulations. In addition, the BF4 adsorped CaCl electrene is a ferromagnetic half-metal with a net magnetic moment of 1  μ B contributed by anionic electrons and a spin-minority bandgap. Thus, the CaCl electrene is a potential candidate for the applications of electron emitter, spin-injector and spintronics. Graphical Abstract: ga1 Highlights: The ground-states of CaCl bulk and monolayer are AB stacking of P 3 ̅ m 1 in which Cl atoms are at Ca-top sites. CaCl bulk is a novel stable vdW semiconducting electride with extremely low interlayer binding energy. CaCl monolayer is a semiconducting electrene with high electron mobility and low work function. Ferromagnetic half-metallicity can be induced by the adsorption of superhalogens BF4 . Magnetism is mainly induced by the anionic electrons of CaCl electrene after the adsorption of superhalogens.